2005
DOI: 10.1002/adfm.200400073
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Doping and Post‐Deposition Treatments on the Conductivity, Morphology, and Work Function of Poly(3,4‐ethylenedioxythiophene)/Poly(styrene sulfonate) Films

Abstract: We investigate the influence of annealing conditions on the physical properties of thin films of poly(3,4‐ethylenedioxythiophene)/poly(styrene sulfonate) (PEDOT/PSS). In particular, we describe how annealing temperature, the ambient gas, and choice of dopant affect the conductivity, morphology, and work function of the films. Two specific dopants are considered, sorbitol and glycerol, and broad guidelines are developed for using PEDOT/PSS as a hole‐injection electrode in polymeric light‐emitting devices, solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
319
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(347 citation statements)
references
References 26 publications
20
319
2
Order By: Relevance
“…This degradation of PEDOT:PSS layer appears to be spatially inhomogeneous and related with the formation of insulating patches causing loss of device current and consequently decrease in device efficiency. Huang et al reported that exposure of the PEDOT:PSS layer to water results in an increase in the resistivity of the device, consistent with previous observations [27]. Polyamide fibers coated with PEDOT-PSS polymer material were also studied for humidity and temperature sensor applications [28].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This degradation of PEDOT:PSS layer appears to be spatially inhomogeneous and related with the formation of insulating patches causing loss of device current and consequently decrease in device efficiency. Huang et al reported that exposure of the PEDOT:PSS layer to water results in an increase in the resistivity of the device, consistent with previous observations [27]. Polyamide fibers coated with PEDOT-PSS polymer material were also studied for humidity and temperature sensor applications [28].…”
Section: Introductionsupporting
confidence: 71%
“…On the other hand, dipole moments of doping materials may also influence the conductivity [27]. Since the water molecule has a considerable dipole moment, the conductivity of PEDOT:PSS may decrease when water is absorbed by PEDOT:PSS [31].…”
Section: Resultsmentioning
confidence: 99%
“…They obviously reduced sheet resistance of the PEDOT:PSS electrode by the treatment of glycerol and sorbitol. Then Bradley et al [50] systematically investigated the effects of thermal annealing, doping and post-treatment on the physical properties (such as morphology, conductivity, and work function) of PEDOT:PSS film. So far doping organic molecules [45,[51][52][53][54][55] in aqueous PEDOT:PSS solution and post-treatment of PEDOT:PSS film with polar organic acid [56][57][58][59][60][61][62][63] are the two most effective approaches for improving the conductivity of PEDOT:PSS films.…”
Section: Conducting Polymer-based Flexible Oscsmentioning
confidence: 99%
“…In addition, the correlation between the morphology and the conductive properties is incompletely understood and has been addressed in a limited number of publications. [10][11][12][13][14][15] Despite large differences in interpretation and experimental data, it is generally believed that charge transport in PE-DOT:PSS occurs by a hopping process. Typically, the resulting conductivity can be described by…”
Section: Introductionmentioning
confidence: 99%